2010
DOI: 10.1093/hmg/ddq407
|View full text |Cite
|
Sign up to set email alerts
|

Sequestration of chaperones and proteasome into Lafora bodies and proteasomal dysfunction induced by Lafora disease-associated mutations of malin

Abstract: Lafora disease (LD) is an autosomal recessive progressive myoclonic epilepsy characterized by the presence of intracellular polyglucosan inclusions commonly known as Lafora bodies in many tissues, including the brain, liver and skin. The disease is caused by mutations in either EPM2A gene, encoding the protein phosphatase, laforin, or EPM2B gene, encoding the ubiquitin ligase, malin. But how mutations in these two genes cause disease pathogenesis is poorly understood. In this study, we show that the Lafora bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 47 publications
5
49
0
Order By: Relevance
“…Nonetheless, our semi-quantitative RT-PCR assay and the Hsp70 promoter reporter assay suggest that loss of laforin or malin does not alter the level of Hsp70-encoding transcripts when the cells are not under stress; therefore, the increased level of Hsp70 protein is probably due to its inefficient clearance from the cellular pool. In this regard, it is interesting that the loss of laforin or malin results in reduced proteasomal activity (Vernia et al, 2009;Rao et al, 2010a). Taken together, the results from the present study suggest that loss of any one of the components of the malinlaforin-CHIP complex affects the ability of the cell to achieve the stress response and might also result in the accumulation of unwanted proteins.…”
Section: Discussionmentioning
confidence: 52%
“…Nonetheless, our semi-quantitative RT-PCR assay and the Hsp70 promoter reporter assay suggest that loss of laforin or malin does not alter the level of Hsp70-encoding transcripts when the cells are not under stress; therefore, the increased level of Hsp70 protein is probably due to its inefficient clearance from the cellular pool. In this regard, it is interesting that the loss of laforin or malin results in reduced proteasomal activity (Vernia et al, 2009;Rao et al, 2010a). Taken together, the results from the present study suggest that loss of any one of the components of the malinlaforin-CHIP complex affects the ability of the cell to achieve the stress response and might also result in the accumulation of unwanted proteins.…”
Section: Discussionmentioning
confidence: 52%
“…60 In contrast, another recent study revealed no changes in LC3-II or other autophagy proteins in brain lysates of another laforin-deficient mouse model, arguing that autophagosome formation and function in the brain of these mice are not critically abnormal. 55 Nevertheless, the recruitment of crucial proteins of the proteasomal, endosomal, and autophagy pathway to LBs, as observed in laforin-deficient mice 55 and brain biopsy tissue of a LD patient, 61 seems to indicate that secondary changes in protein degradation pathways are important contributors to neuronal pathology.…”
Section: Autophagy In Pediatric Brain Diseasesmentioning
confidence: 99%
“…This is further supported by some recent studies indicating the role of either laforin or malin in cell survival pathways (19,20). Emerging evidence now points toward the defect in intracellular protein degradation pathways in LD pathogenesis (21)(22)(23)(24). Because malin is an ubiquitin ligase, its loss of function could result in improper clearance and accumulation of its target substrates, leading to the pathogenesis of LD.…”
mentioning
confidence: 66%